2007
DOI: 10.3310/hta11060
|View full text |Cite
|
Sign up to set email alerts
|

Oral naltrexone as a treatment for relapse prevention in formerly opioid-dependent drug users: a systematic review and economic evaluation

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. NHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 62 publications
3
52
0
Order By: Relevance
“…Three quarters of the patients who were successful in their detoxification attempt commenced naltrexone therapy, but only half were still taking the medication 1 month later; and only two, at the 6-month follow-up. This is consistent with previous studies of unsupervised naltrexone prescribing as a relapse prevention measure (Adi et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…Three quarters of the patients who were successful in their detoxification attempt commenced naltrexone therapy, but only half were still taking the medication 1 month later; and only two, at the 6-month follow-up. This is consistent with previous studies of unsupervised naltrexone prescribing as a relapse prevention measure (Adi et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…As an antagonist, it does not provoke a biological response when it binds to the opioid receptors, but instead it blocks or dampens agonistmediated responses, blocking the euphoric effects of heroin and other opioids, helping patients to maintain abstinence from opioid drugs. 3 A number of systemic reviews and meta-analyses have examined the efficacy of naltrexone in people who are dependent on opioid drugs. These reviews have concluded that naltrexone appears to have some benefit in the management of opioid dependence; however, the heterogeneity of trials makes objective evaluation difficult.…”
Section: Original Papersmentioning
confidence: 99%
“…These reviews have concluded that naltrexone appears to have some benefit in the management of opioid dependence; however, the heterogeneity of trials makes objective evaluation difficult. [3][4][5][6][7] The aim of this study was to use a retrospective casenote study to rigorously assess and identify other potential predictors for longer-term retention on naltrexone maintenance therapy. The case notes were also used to evaluate the overall rate of retention in treatment in a large UK community drug clinic.…”
Section: Original Papersmentioning
confidence: 99%
“…These reviews have concluded that naltrexone appears to have some benefit in the management of opioid dependence; however, the heterogeneity of trials makes objective evaluation difficult. [3][4][5][6][7] The aim of this study was to use a retrospective casenote study to rigorously assess and identify other potential predictors for longer-term retention on naltrexone maintenance therapy. The case notes were also used to evaluate the overall rate of retention in treatment in a large UK community drug clinic.…”
mentioning
confidence: 99%